SOCIALIZATION OF HOSPITAL MANAGEMENT INFORMATION SYSTEMS IN PATIENT SAFETY AND HEALTH (Jurnal Abdimas Administrasi Kesehatan, 2022)
All medical actions against patients must have their own risks. Certainly not a single health worker or doctor would want his patient to experience this unwanted risk. Therefore, patient safety must be prioritized in every medical treatment. Every medical staff must understand it, so they can apply it properly. Patient safety is of key importance to any health facility. Hospital management information systems in patient safety and health activities were held on December 20-23, 2021, RSIA Jimmy Medika Borneo. This community service aims to provide knowledge to the public about management information systems in hospitals, provide knowledge about existing services in hospitals and how to get excellent service. The results obtained from community service are that the community. The community also understands the services available at the hospital and how to get excellent service. For continuation, it is recommended to carry out further on this guidance approach on a broader subject, easier material and more relevant methods so that generalizations can be drawn.